2015
DOI: 10.1080/10426507.2014.1002615
|View full text |Cite
|
Sign up to set email alerts
|

Aziridines Ring Opening by Silyl Chalcogenides: a Stereoselective Access to Polyfunctionalized Molecules as Precursor of Sulfurated and Selenated Heterocycles

Abstract: Aziridines react efficiently with bis(trimethyl)silyl-sulfide and -selenide to afford a direct access to β-amino thiols and selenols. Synthesis of 2,4-disubstituted 1,3-selenazolidines is obtained through reaction of 1,2-amino selenols with aldehydes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…In order to evaluate the scope of this procedure, a chiral β-amino thiol 5, obtained from aziridine and HMDST 12 , was reacted with the bromo ester under similar conditions, affording the Ts-protected α-thio-δ-amino esters 6 (Scheme 1, Expanding the scope of this procedure to seleno analogues, we found that the precursor β-hydroxy selenide 10 could be achieved by treatment of selenol (obtained from the epoxide and (TMS) 2 Se 9) 19 with the bromo ester (Scheme 2) under Cs 2 CO 3 /TBAI activation. Treatment with DIBAL-H directly afforded differently 6-substituted 2-hydroxy 1,4-oxaselenolanes 11 as mixture of stereoisomers 20 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the scope of this procedure, a chiral β-amino thiol 5, obtained from aziridine and HMDST 12 , was reacted with the bromo ester under similar conditions, affording the Ts-protected α-thio-δ-amino esters 6 (Scheme 1, Expanding the scope of this procedure to seleno analogues, we found that the precursor β-hydroxy selenide 10 could be achieved by treatment of selenol (obtained from the epoxide and (TMS) 2 Se 9) 19 with the bromo ester (Scheme 2) under Cs 2 CO 3 /TBAI activation. Treatment with DIBAL-H directly afforded differently 6-substituted 2-hydroxy 1,4-oxaselenolanes 11 as mixture of stereoisomers 20 .…”
Section: Resultsmentioning
confidence: 99%
“…[29b] Benzeneselenol is commercially available. β‐Substituted selenols were prepared according to the procedure developed in one of our groups . l ‐Cysteine methyl ester hydrochloride, l ‐methionine methyl ester hydrochloride, and cysteamine were purchased from Aldrich and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…GPx-like activity was determined according to a reported NMR assay [28][29][30]. DTT red (0.14 mmol) and catalyst (0.014 mmol) were dissolved in CD 3 OD (0.6 mL), and the solution was added to 35% H 2 O 2 (14 µL, 0.14 mmol) to start the reaction.…”
Section: Gpx-like Catalytic Activity Measurmentsmentioning
confidence: 99%
“…. Het (N, O) interactions [23].Owing to the interest in these selenium containing compounds, the search for novel procedures to prepare small molecules containing the Se-S unit is of great interest.Our long-dated interest in the chemistry of silyl chalcogenides allowed to disclose novel procedures to access a plethora of sulfur and selenium containing molecules exploiting the nucleophilic behaviour of the chalcogen atom towards various electrophiles [24][25][26][27][28][29]. Recently we reported the reaction of bis(trimethylsilyl)selenide (HMDSS) with N-thiophtalimides as a mild, general metal free procedure for the synthesis of variously substituted disulfides [30].Indeed, despite the interest in the reactivity of selenols as nucleophilic selenium transfer reagents, their use has been critically limited by their instability.…”
mentioning
confidence: 99%
See 1 more Smart Citation